Performance Analysis of Space-Time Line Code with Imperfect Channel Estimation - Pang, Yashan; Lei, Xia; Xiao, Yue (IEEE Vehicular Technology Conference, 2023)
Space-time line code (STLC) constitutes an attractive multiple-input multiple-output (MIMO) transmission scheme conceived for full diversity gain, while reducing the complexity of the receiver substantially. In this paper, we investigate the influence of imperfect channel estimation to STLC when the channel is modeled by Rayleigh and Rician fading. Furthermore, based on the derived the signal-to-interference-plus-noise ratio (SINR), both the theoretical bit-error-rate (BER) bound and the outage probability of STLC are quantified subject to channel estimation errors. The numerical results finally confirm the reliability of the theoretical analysis.